Bis(2-ethoxy-6-formylphenolato-κ(2) O (1),O (6))nickel(II) - Han, Zhen-Quan (International Union of Crystallography, 2008)
The title compound, [Ni(C(9)H(9)O(3))(2)], was synthesized by the reaction of 3-ethoxysalicylaldehyde with nickel(II) nitrate in methanol solution. The asymmetric unit onsists of two half-molecules; each Ni atom lies on a centre of symmetry. The Ni(II) ions are coordinated by four O atoms from two deprotonated 3-ethoxysalicylaldehyde ligands in a slightly distorted square-planar coordination environment.